Common errors analysis in solving problems of fractional number reviewed from Newman's theory - Priwantoro, Soffi Widyanesti; Monica, Vina; Fauzia, Nabila Atika; Larasati, Larasati (Universitas Ahmad Dahlan, 2023)
This research aims to describe common mistakes made by students in calculating fractional numbers, especially in comparing fractional numbers. For this reason, an analysis of the mistakes made by students is required. The subjects in this research were three students of SMP Muhammadiyah 1 Godean who were taken after fulfilling the requirements for selecting research subjects. Test and observation methods are the methods for collecting data. The data analysis technique used in this research is Newman's theory, of which there are 5 stages, namely: (1) reading stage, (2) understanding stage, (3) transformation stage, (4) process skills stage, and (5) Answer Writing Stage. This research shows that the errors made by students in general are: (1) Errors in reading and understanding questions, (2) Errors in reading mathematical comparison symbols, (3) Errors in changing the form of images presented to fractional numbers, and (4) Errors in calculating the LCM value between two denominators.